An Evaluation Study of Scientific Approach in English Language Teaching at Grades VII in SMP Negeri 2 Singaraja - ., I Gede Guna Parmanto; ., Dewa Ayu Eka Agustini, S.Pd., M.S.; ., I Nyoman Pasek Hadi Saputra, S.Pd., M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
The study aimed to (1) evaluate the implementation of scientific approach in the seventh grade performed by the English teachers at SMP Negeri 2 Singaraja, and (2) find out the problems that appeared during the implementation of scientific approach in seventh grade English teachers of SMP Negeri 2 Singaraja. The subjects of this study were two English teachers of the seventh grade at SMP Negeri 2 Singaraja. This study employed evaluation study using CIPP model. This study evaluated the implementation of scientific approach in forms of context and process. The techniques for collecting data were observation and interview. The result of the data showed that context evaluation was relevant to the lesson plan components in curriculum 2013. Meanwhile, in form of the process, both of the teachers conducted the relevant learning activities using scientific approach. But, it was not relevant to the lesson plan that they had arranged. The problems that were encountered by the teachers are in making assessment and inserting activity when they designed the lesson plan using scientific approach. In the implementation, encouraging students to ask questions and the limitation of times become problems in teaching and learning process using scientific approach. keyword : Curriculum 2013, Scientific Approach, Evaluation